TAX AUTOMATION AND DATA INTELLIGENCE: THE NEW ERA OF EFFICIENCY IN CORPORATE ACCOUNTING - Silva, Karina da Fonseca Inacio (LUMEN ET VIRTUS, 2024)
This article analyzes the impact of tax automation and data intelligence on the efficiency of corporate accounting. It explores how emerging technologies—such as Robotic Process Automation (RPA) and Artificial Intelligence (AI)—are transforming tax compliance, minimizing manual errors, and providing valuable strategic support for organizations. Through a qualitative discussion of recent academic studies and real cases, the text highlights benefits such as cost reduction, improved accuracy, and enhanced decision-making. The article also addresses technological challenges and the need for new professional competencies in the accounting field. The findings indicate that the integration of automation and data intelligence not only streamlines processes but also positions accountants as strategic partners in corporate management.